Analysis and Development of Marketing for the Creative Industry of West Sumatra Based on E-Commerce with the Concept of Customer Relationship Management (Crm) (Analisa Dan Pengembangan Pemasaran Industri Kreatif Sumatera Barat Berbasis E-Commerce Dengan K - Dinul Akhiyar; Vivi Nila Sari; Abulwafa Muhammad (Jurnal KomtekInfo, 2019)
West Sumatra is an area in Indonesia that has many Creative Industries, this is the reason the government places representatives of the Ministry of Creative Industries in this region. This is done to foster, oversee and develop the Creative Industries that exist today. The Creative Industries that exist today are very diverse there are 15 fields that are very potential to be developed in Indonesia, Advertising (Advertising), Architecture, Art Goods Market, Crafts (Craf), Design, Video, Film, Photography, Interactive Games (Games), Music , Performing Arts (Showbiz), Publishing and Printing, Computer and Software Services, Television and Radio (Broadcasting), Research and Development (R&D), Culinary. Of the 15 creative industries in Indonesia for the West Sumatra region there are 9 sub-sectors of potential creative industries, namely, fashion, culinary, handicraft, music, performing arts, photography, design, animation, and film, but not all creative industry sectors it is developing so that it has an impact on the marketing of its products. For this reason, it is necessary to analyze and develop the marketing of creative industries in West Sumatra that prioritizes the concept of Customer Relationship Management (CRM) so that marketing concepts that have the potential to increase marketing of creative industry products will be known. Especially now that the Provincial Government is developing the Halal Tourism Industry, of course in this field there a re very many opportunities for the development of the Creative Industries